2015
DOI: 10.1038/nature14583
|View full text |Cite|
|
Sign up to set email alerts
|

Progesterone receptor modulates ERα action in breast cancer

Abstract: Summary Progesterone receptor (PR) expression is employed as a biomarker of estrogen receptor-α (ERα) function and breast cancer prognosis. We now show that PR is not merely an ERα-induced gene target, but is also an ERα-associated protein that modulates its behaviour. In the presence of agonist ligands, PR associates with ERα to direct ERα chromatin binding events within breast cancer cells, resulting in a unique gene expression programme that is associated with good clinical outcome. Progesterone inhibited e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
530
5
13

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 533 publications
(588 citation statements)
references
References 40 publications
30
530
5
13
Order By: Relevance
“…In the presence of both estrogen and progesterone, PGR was shown to be recruited to the ESR1 complex and to redirect ESR1-binding events, resulting in a gene expression profile associated with better clinical outcome (Mohammed et al 2015). However, in the presence of estrogen alone, un-liganded PGRB activated a subset of ER target genes by acting as a molecular scaffold for the formation of a transcriptional complex with ESR1 and PELP1, resulting in a more aggressive proliferative response to estrogen (Daniel et al 2015).…”
Section: Combinatorial Control Of Gene Expression By Nrs In Breast Camentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of both estrogen and progesterone, PGR was shown to be recruited to the ESR1 complex and to redirect ESR1-binding events, resulting in a gene expression profile associated with better clinical outcome (Mohammed et al 2015). However, in the presence of estrogen alone, un-liganded PGRB activated a subset of ER target genes by acting as a molecular scaffold for the formation of a transcriptional complex with ESR1 and PELP1, resulting in a more aggressive proliferative response to estrogen (Daniel et al 2015).…”
Section: Combinatorial Control Of Gene Expression By Nrs In Breast Camentioning
confidence: 99%
“…Further, they showed that ESR1 binding is a highly dynamic process, with distinct ESR1-binding regions observed in samples with different outcomes. This dynamic change in ESR1 action was shown to be influenced by the action of other NRs, such as PGR (Mohammed et al 2015), as well as the signaling context leading to ESR1 activation. For example, ESR1 displayed distinct genomic binding profiles depending on whether ESR1 was activated by estrogen or through the epidermal growth factor (EGF) pathway (Lupien et al 2010).…”
Section: Reprogramming Of Nr Binding and Disease Progressionmentioning
confidence: 99%
“…We have previously shown that PGR is not only an ERα‐target gene but is also an ERα‐associated protein that can reprogram ERα DNA binding and transcriptional responses in breast cancer and, importantly, used the PDE model to study the transcriptome and growth effects of this ERα reprogramming by PGR (Mohammed et al ., 2015; Singhal et al ., 2016). To further investigate these findings, herein we report successful ERα ChIP‐seq in ERα‐positive breast cancer PDEs cultured with E2 in the presence or absence of synthetic PGR agonist R5020.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the heterogeneity we observed is likely representative of individual tissue microenvironments, and the PDE model provides an avenue to more accurately dissect how the tumor setting influences ERα signaling. In support of this concept, we used genomewide profiling of hormone‐treated breast cancer PDEs to capture ERα binding events and demonstrated reprogramming of ERα binding by synthetic progestin R5020, a phenomenon we recently reported using cell line models and clinical samples (Mohammed et al ., 2015; Singhal et al ., 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Developing new drugs that extinguish ER activity is the current vogue to improve treatment outcomes. Recent work (Mohammed et al 2015) supports a novel approach, whereby the activation of the progesterone receptor (PR) redirects oestrogen-stimulated ER to genomic loci associated with better disease outcomes. In that study, it was also revealed that PR loss is a common event, especially in the luminal B subtype of ER-positive disease.…”
mentioning
confidence: 99%